Primordial Abstraction of Voice over Internet Protocols (VoIP) - Misha,; Kaur, Dalveer (International Journal of Computer Sciences and Engineering, 2019)
This paper include the study of voice over internet protocol, its architecture that how VoIP works , issues that occur in voice over internet protocol , VoIP codecs and many more .In the era of wireless communication technologies, the actual time services which includes data as voice (i.e Voice Over Internet Protocol ) is growing stupendously. Different applications of VoIP which includes SKYPE, GOOGLE TALK, etc. are used to provide economical voice calls to the end users. VoIP is technology used for communication so as to transmit voice and data over internet protocols. VoIP is used for IP telephony services which includes voice messaging ,calling, video messaging as well as video conferencing etc.